IMPLEMENTATION OF ARTICLE 27 SECTION (1) OF LAW NUMBER 24 OF 2013 CONCERNING POPULATION ADMINISTRATION YEAR 2013 CONCERNING POPULATION ADMINISTRATION - Yusran Gea, Ali; Andoko, Andoko (Proceeding International Seminar of Islamic Studies, 2023)
There are two problems studied in this research, namely: (1) How Implementation of Article 27 Paragraph (1) of Law Number 24 of 2013 concerning Population Administration in Manau Sembilan Village II Population Administration in Manau Sembilan II Village, Padang Guci District Hulu Kaur Regency, and (2) How does Islam view the community that does not fulfill the right to identity of children in Manau Sembilan II Village? who do not fulfill the right to a child's identity in Manau Sembilan II Village, Padang Guci Hulu Subdistrict, Kaur Regency. Padang Guci Hulu Kaur Regency. To reveal the above problems, the The research method used is descriptive qualitative research, exploring data, information about the Implementation of Article 27 Paragraph (1) of Law Number 24 Year 2013 concerning Population Administration (Study in Manau Sembilan Village II Subdistrict Padang Guci Hulu Kaur Regency by using the method of Field Risearch is a research conducted in the field with observation, interviews and documentation. observation, interviews and documentation. Then described analyzed, and discussed to answer the problem. The results of this study found that: 1. Article 27 Paragraph (1) of Law Number 24 of 2013 Concerning Population Administration (Study in Manau Sembilan II Village, Padang Guci Hulu Subdistrict) Population Administration (Study in Manau Sembilan II Village, Padang Guci Hulu Subdistrict, Kaur Regency) has not been implemented optimally. Islam does not prohibit the registration of children's births because the registration of children's births is not allowed. If the birth of a child is registered because birth registration aims to bring maslahat for the child. maslahat for the child. So that people who have not reported births and have not taken care of Birth Certificate to be able to take care of it while still following the provisions of the State law.